2021
DOI: 10.1002/ar.24642
|View full text |Cite
|
Sign up to set email alerts
|

Scaling and relative size of the human, nonhuman ape, and baboon calcaneus

Abstract: Among human and nonhuman apes, calcaneal morphology exhibits significant variation that has been related to locomotor behavior. Due to its role in weight-bearing, however, both body size and locomotion may impact calcaneal morphology. Determining how calcaneal morphologies vary as a function of body size is thus vital to understanding calcaneal functional adaptation. Here, we study calcaneus allometry and relative size in humans (n = 120) and nonhuman primates (n = 278), analyzing these relationships in light … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 7 publications
(20 citation statements)
references
References 85 publications
(172 reference statements)
5
15
0
Order By: Relevance
“…Nevertheless, sexual dimorphism of the calcaneus size increased with the transition to a sedentary lifestyle. This might be related to the positive association between body mass and calcaneus size (Harper et al, 2022a). The overlap in variance between males and females in calcaneal indices with only a few significant differences (LAW/MaxL, LAL/MaxL, and CFB/CFH) corresponded with previous findings demonstrating no significant differences in calcaneal shape between the sexes (Harper, 2023).…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…Nevertheless, sexual dimorphism of the calcaneus size increased with the transition to a sedentary lifestyle. This might be related to the positive association between body mass and calcaneus size (Harper et al, 2022a). The overlap in variance between males and females in calcaneal indices with only a few significant differences (LAW/MaxL, LAL/MaxL, and CFB/CFH) corresponded with previous findings demonstrating no significant differences in calcaneal shape between the sexes (Harper, 2023).…”
Section: Discussionsupporting
confidence: 85%
“…Furthermore, the human calcaneus had to adapt to higher ground reaction force applied to it at heel strike (Latimer and Lovejoy, 1989). These adaptations included an asymmetric and convex cuboid facet, a broader and shorter calcaneal tuberosity, and a larger lateral plantar process, which was more plantarly positioned compared to apes (Bojsen-Møller, 1979;Latimer and Lovejoy, 1989;Boyle et al, 2018;Harper et al, 2021;Harper et al, 2022a). Furthermore, it has been suggested that human calcaneal morphology of shorter calcaneal tuber (body) improves running economy (Raichlen et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…as calcaneal tuber breadth scales to estimated body mass with positive allometry in both modern humans and nonhuman primates (Harper et al, 2022). The KW 6302 calcaneal robusticity index is close to what is preserved in A. africanus, another smallbodied hominin (Prang, 2015;Ruff et al, 2018), indicating that the two specimens may have experienced similar loading regimes.…”
Section: Functional Considerationsmentioning
confidence: 68%
“…Gorillas have been recently shown to use a heel‐only heel strike with an impact spike, however, suggesting that KW 6302 may have utilized a modern human‐like heel strike (Zeininger et al, 2019; Wunderlich et al, 2019). The relatively narrow tuber may also be the product of KW 6302′s small body size (reconstructed to be 33.3–35.9 kg) as calcaneal tuber breadth scales to estimated body mass with positive allometry in both modern humans and nonhuman primates (Harper et al, 2022). The KW 6302 calcaneal robusticity index is close to what is preserved in A. africanus, another small‐bodied hominin (Prang, 2015; Ruff et al, 2018) , indicating that the two specimens may have experienced similar loading regimes.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation